Serum transferrin polymorphism and their association with economic traits in Sahiwal and Jersey x Sahiwal crosses* - SHRIRAO, V R; KOTHEKAR, M D; DESHMUKH, S N; GORE, A K; MANGLE, N S (The Indian Journal of Animal Sciences, 2013)
Serum samples (87) from Sahiwal and its crosses were analysed for transferrin types using polyacrylamide gel electrophoresis (PAGE) method. Samples were drawn from 30 Sahiwal, 43 Jersey x Sahiwal and 14 Karan-Swiss x Jersey x Sahiwal genetic groups. On the basis of mobility TfA TfD and TfE were observed. Chi-square values indicated nonsignificant difference between different phenotypes within the genetic groups. The gene frequency ranged between 00.14 for TfE to 0.36 TfA. Comparison of dam daughter revealed presence of I allele of parent in of fspring. Least-squares analysis showed nonsignificant contribution of different transferrin types in age at first calving, first calving interval and breeding efficiency, However, cows with TfD genotypes had higher first 300-days milk yield.